A novel approach to realize SANI process in freshwater sewage treatment – Use of wet flue gas desulfurization waste streams as sulfur source - Jiang, Feng; Zhang, Liang; Peng, Guo-Liang; Liang, Si-Yun; Qian, Jin; Wei, Li; Chen, Guang-Hao (Water research (Oxford), 2013)
SANI (Sulfate reduction, Autotrophic denitrification and Nitrification Integrated) process has been approved to be a sludge-minimized sewage treatment process in warm and coastal cities with seawater supply. In order to apply this sulfur-based process in inland cold areas, wet flue gas desulfurization (FGD) can be simplified and integrated with SANI process, to provide sulfite as electron carrier for sulfur cycle in sewage treatment. In this study, a lab-scale system of the proposed novel process was developed and run for over 200 days while temperature varied between 30 and 5 °C, fed with synthetic FGD wastewaters and sewage. The sulfite-reducing upflow anaerobic sludge bed (SrUASB) reactor, as the major bioreactor of the system, removed 86.9% of organics while the whole system removed 94% of organics even when water temperature decreased to around 10 °C. The bactericidal effect of sulfite was not observed in the SrUASB reactor, while thiosulfate was found accumulated under psychrophilic conditions. The sludge yield of the SrUASB reactor was determined to be 0.095 kg VSS/kg COD, higher than of sulfate reduction process but still much lower than of conventional activated sludge processes. The dominant microbes in the SrUASB reactor were determined as Lactococcus spp. rather than sulfate-reducing bacteria, but sulfite reduction still contributed 85.5% to the organic carbon mineralization in this reactor. Ammonia and nitrate were effectively removed in the aerobic and anoxic filters, respectively. This study confirms the proposed process was promising to achieve sludge-minimized sewage treatment integrating with flue gas desulfurization in inland and cold areas. •Sewage mixed with FGD waste streams can achieve sludge-minimized sewage treatment.•FGD-SANI system ensures high organic removal efficiency in cold weather.•Efficiently nitrification and denitrification can be made by the proposed process.•Thiosulfate accumulates in sulfite reduction under psychrophilic conditions.